ZnO-beta zeolite: as an effective and reusable heterogeneous catalyst for the one-pot synthesis of polyhydroquinolines - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Green Chemistry Letters and Reviews, 2010)
ZnO-beta zeolite, an inexpensive and mild catalyst, has been used for the synthesis of polyhydroquinolines in excellent yields from the one-pot four-component condensation of aldehydes, dimedone, ethyl acetoacetate, and ammonium acetate in ethanol at room temperature. The remarkable advantages offered by this method are a green catalyst, mild reaction conditions, simple work-up procedures, much faster reactions, and excellent yield of products. Furthermore, the catalyst could be reused several times keeping its initial activity in recycled reactions.
Keywords: Hantzsch condensation; heterogeneous catalyst; multicomponent; ZnO-beta zeolite

ZnO-beta zeolite mediated simple and efficient method for the one-pot synthesis of quinoxaline derivatives at room temperature - Katkar, Santosh S.; Mohite, Pravinkumar H.; Gadekar, Lakshman S.; Arbad, Balasaheb R.; Lande, Machhindra K. (Central European Journal of Chemistry, 2010)
A rapid and an efficient one-pot method for the synthesis of quinoxalines catalysed by ZnO-beta zeolite at room temperature is described. This environmentally benign method provides several advantages over methods that are currently employed such as a simple work-up, mild reaction conditions, good to excellent yields, and a process to recover and reuse the catalyst for several cycles with consistent activity.
Keywords: cyclocondensation; Quinoxaline; Room temperature; ZnO-beta zeolite